Plasmacytoid dendritic cells and type 1 interferon promote peripheral expansion of forkhead box protein 3+ regulatory T cells specific for the ubiquitous RNA‐binding nuclear antigen La/Sjögren's syndrome (SS)‐B. (3rd August 2016) - Pan, Z.‐J.; Horton, C. G.; Lawrence, C.; Farris, A. D.
Summary: RNA‐binding nuclear antigens are a major class of self‐antigen to which immune tolerance is lost in rheumatic diseases. Serological tolerance to one such antigen, La/Sjögren's syndrome (SS)‐B (La), is controlled by CD4 + T cells. This study investigated peripheral tolerance to human La (hLa) by tracking the fate of hLa‐specific CD4 + T cells expressing the transgenic (Tg) 3B5.8 T cell receptor (TCR) after adoptive transfer into lymphocyte‐replete recipient mice expressing hLa as a neo‐self‐antigen. After initial antigen‐specific cell division, hLa‐specific donor CD4 + T cells expressed forkhead box protein 3 (FoxP3). Donor cells retrieved from hLa Tg recipients displayed impaired proliferation and secreted interleukin (IL)−10 in vitro in response to antigenic stimulation. Transfer of highly purified FoxP3‐negative donor cells demonstrated that accumulation of hLa‐specific regulatory T cells (Treg ) was due primarily to expansion of small numbers of donor Treg . Depletion of recipient plasmacytoid dendritic cells (pDC), but not B cells, severely hampered the accumulation of FoxP3 + donor Treg in hLa Tg recipients. Recipient pDC expressed tolerogenic markers and higher levels of co‐stimulatory and co‐inhibitory molecules than B cells. Adoptive transfer of hLa peptide‐loaded pDC into mice lacking expression of hLa recapitulated the accumulation of hLa‐specific Treg . Blockade of the type 1 interferon (IFN) receptor in hLa Tg recipients of hLa‐specific T cells impaired FoxP3 + donor T cell accumulation. Therefore, peripheral expansion of Treg specific for an RNA‐binding nuclear antigen is mediated by antigen‐presenting pDC in a type 1 IFN‐dependent manner. These results reveal a regulatory function of pDC in controlling autoreactivity to RNA‐binding nuclear antigens.